A correction and addition to Zwick (2023): A new subgenus of Neoperla (Plecoptera, Perlidae) - Zwick, Peter (Zootaxa, 2024)
A male lectotype and female paralectotypes of Neoperla (Oodeia) dolichocephala Klapálek, 1909, new status, are designated and illustrated. Notes on other species in the subgenus are added.